Outcomes of bone morphogenetic protein-2 and iliac cancellous bone transplantation on alveolar cleft bone grafting: A meta-analysis. Issue 6 (June 2020) - Xiao, Wen-lin; Jia, Kai-ning; Yu, Guo; Zhao, Ning
Summary: Background: To systematically evaluate the effect of bone morphogenetic protein-2 (BMP-2) and iliac cancellous bone graft (ICBG) on alveolar cleft bone grafting (ACBG) in cleft lip and palate. Method: Online databases were searched for case-control studies related to the application of BMP-2 and ICBG in ACBG. Result: Meta-analysis showed no significant statistical difference in the filling rate (OR = 4.1, 95% CI (0.06, 2.63)), the volume of bone graft area (OR=−0.42, 95% CI (−1.44, 0.60)), the height of bone graft area (OR = −21.38, 95% CI (−23.00, −19.76)), the density of bone graft area (OR = 0.43, 95% CI (−0.79, 1.64)), the failure rate of bone graft (OR = 0.02, 95% CI (−0.03, 0.06)), infection after operation, and the rate (OR = 0.20, 95% CI (0.05, 0.73)) and the incidence of postoperative oronasal fistula (OR = 4.1, 95% CI (0.06, 2.63)) between BMP-2 and ICBG in ACBG. However, there were obvious statistical differences in operative time (OR = −3.64, 95% CI (−7.35, 0.06)) and the length of hospital stay (OR = −1.97, 95% CI (−2.41, −1.53)). Conclusion: The meta-analysis shows that there is no significant difference between BMP-2 and ICBG in filling rate, volume, density, failure rate, and the occurrence of oronasal fistula after ACBG. There were significant differences between BMP-2 and ICBG in the operation time and hospitalization time of ACBG. Compared with ICBG bone graft, BMP-2 has more advantages in ACBG such as remaining area height, postoperative infection rate, operative time, and length of hospital stay.